Caffeic Acid Inhibited Receptor Activator of Nuclear Factor kappaB Ligand (RANKL)-Tumor Necrosis Factor (TNF) alpha-TNF Receptor Associated Factor (TRAF) 6 induced Osteoclastogenesis Pathway - Ferry Sandra; Toshio Kukita; Tatsushi Muta; Tadahiko Iijima (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Caffeic acid was reported in our previous study to have potential in inhibiting osteoclastogenesis through inhibition of nuclear factor κB (NFκB). Here in our current study, we would like to investigate further the caffeic acid-affected signaling pathway leading to NFκB inhibition. Since tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) plays important role in osteoclastogenesis, we applied TRAF6- transfected RAW264 cells D-Clone (RAW-D) cells as model in this study.METHODS: Caffeic acid in various concentrations was added to in vitro osteoclastogenesis of receptor activator nuclear factor κB ligand (RANKL)-TNFα-induced TRAF6-transfected RAW-D cells. Cells were collected, lysed and immunoblotted to detect TRAF6 expression. To detect tartrate resistant acid phosphatase (TRAP)+ polynucleated cells (PNCs), TRAP staining was performed. Meanwhile, to measure NFκB Activity, cells were transfected with pNFκB-TA-Luc and subjected to Dual Luciferase Reporter Assay System.RESULTS: Caffeic acid did not influence TRAF6 expression of RANKL-TNFα-induced TRAF6-transfected RAW-D cells. Caffeic acid diminished NFκB activity of RANKL-TNFα-induced TRAF6-transfected RAW-D cells in a concentration dependent manner. Significant NFκB activity inhibitions were seen under treatment of 1 and 10 μg/ml caffeic acid. By adding 10 μg/ml caffeic acid in RANKL-TNFα-induced TRAF6-transfected RAW-D cells, TRAP+ PNCs number was significantly suppressed.CONCLUSION: Caffeic acid inhibited RANKL-TNFα-TRAF6-induced osteoclastogenesis pathway. Since caffeic acid did not influence TRAF6 expression, TRAF6-RANK interactions and/or TRAF6 downstream signaling pathway should be further pursued to disclose inhibition mechanism of caffeic acid.KEYWORDS: caffeic acid, osteoclastogenesis, TRAF6, RANKL, TNFα, NFκB, RAW-D